Penguatan Peran Tour Guide Dalam Memasarkan Objek Wisata di Kecamatan Silian Raya di Kabupaten Minahasa Tenggara - Margaretha Nova Warokka; Radjab Djamali (HOSPITALITI DAN PARIWISATA, 2021)
The purpose of this research is to empowered the community, in this case Tour Guide in introducing tourism object in South West Minahasa Regency, especially Silian Raya District and to empowered them through their skill as a Marketing Agent in increasing tourists to come to this area, and the third, is to boost the community economy by participating in community businesses in tourism field, which are cooperated with BUNDES. This is due to no marketing strategy that suit to sell the tourism objects by the businessmen in Kecamatan Silian Raya Kabupaten Minahasa Tenggara. The previous marketing strategy through promotion that was implemented not well planned, takes some efforts and steps to synchronize, so the visitationsof tourist will increase.The method of this research used here is descriptive qualitative. Descriptive research is used to get the descriptions of role of Tour guide in increasing the tourist in Kecamatan Silian Raya, while to collect the data in this research are as follow, firstly, through interview to the businessmen, secondly, through observations, that is to observe directly about the existence of tourist in this district, thirdly through documentation which record all of the activity & the tourism objects.The outcome of this research is to put on an acreditate journal such as Hospitality and Tourism journal